Evaluation of 18F-FDG uptake in lung parenchyma compensating for tissue fraction: Comparison between non-enhanced low dose CT and intravenous contrast-enhanced diagnostic CT - Garpered, Sabine; Minarik, David; Frantz, Sophia; Valind, Sven; Wollmer, Per (Nuklearmedizin - NuclearMedicine, 2020)
Aim To determine how the presence of intravenous (IV) contrast-enhanced CT influences SUV measurements corrected for both attenuation and tissue fraction.Material and Methods Eighteen patients with different malignancies, free from lung disorders, lung cancer or metastasis, were prospectively recruited when referred for staging with combined 18F-FDG-PET/CT examination. A non-enhanced low-dose CT over the chest was immediately followed by a whole-body IV contrast-enhanced diagnostic CT and finally the PET acquisition. PET data were reconstructed with attenuation correction based on the two CT data sets. The lungs were segmented in the CT images and lung density was measured. Uptake of 18F-FDG in lung parenchyma was recorded using both non-enhanced and IV contrast-enhanced CT as well as with and without compensation for lung aeration. A comparison of SUV values of corrected and uncorrected PET images was performed.Results There was no significant difference between low dose PET/CT and IV contrast-enhanced PET/CT when removing the impact of air fraction (p = 0.093 for the right lung and p = 0.085 for the left lung). When tissue fraction was not corrected for, there was a significant difference between low dose PET/CT and IV contrast enhanced PET/CT used for attenuation correction (p = 0.006 for the right lung and p = 0.015 for the left lung).Conclusion There was only a marginal effect on the assessement of SUV in the lung tissue when using IV contrast enhanced CT for attenuation correction when the air fraction was accounted for.
Keywords: PET/CT; attenuation correction; lung parenchyma; IV contrast agent